Pengaruh Bimbingan Karir Berbasis Mind Map Dalam Meningkatkan Perencanaan Karir Siswa Di SMA Negeri 12 Banjarmasin - Lisa Yuliana; Farial Farial; Sri Ayatina Hayati (Primary Journal of Multidisciplinary Research, 2026)
Career guidance is indispensable because it is the first step in career decision-making. This study aims to determine the influence of mind map- based career guidance in improving the career planning of SMA Negeri 12 Banjarmasin students. The method used is pre-experimental with One Group Pretest-Posttest Design. The research sample amounted to 29 students who took the pretest and 15 students who were used as treatment subjects. The data collection technique used a career planning questionnaire. The data analysis technique used the Kolmogorov-Smirnov normality test and the t-test (paired sample t-test). The results showed an increase in the average score from 97.50 in the pretest to 110.70 in the posttest. The paired test of the t-Test sample showed a significance value of 0.000 < 0.05, which means that mind map-based guidance has an effect on improving students' career planning.